Bipolar doping of double-layer graphene vertical heterostructures with hydrogenated boron nitride1. Issue 17 (7th May 2015) - Liu, Zhun; Wang, Ru-Zhi; Liu, Li-Min; Lau, Woon-Ming; Yan, Hui
<x xml:space="preserve">Abstract</x> Using first-principles calculations, we examined the bipolar doping of double-layer graphene vertical heterostructures, which are constructed by hydrogenated boron nitride (BN) sheets sandwiched into two parallel graphene monolayers.